Towards All-Integrated Optical Nanometrology - Beck, Paul; Schulz, Sebastian A.; Bag, Ankan; Morichetti, Francesco; Banzer, Peter (Optics InfoBase Conference Papers, 2021)
We discuss an all-integrated photonic chip for high-precision localization and other nanometrological tasks. The proposed photonic device drastically reduces the footprint of previous techniques and involves bespoke components and detection schemes.
CRIS-Team Scopus Importer:2024-12-16